(untitled) (Mugda Medical College Journal, 2023)
Background: Observation of variability of lactate levels instead of mean lactate level in critically ill patients with sepsis act as more efficient mortality factor. Objective: To determine whether lactate levels measured at different intervals can predict mortality more effectively than that of mean lactate level for septic patients in intensive care unit (ICU). Methods: This cross-sectional study was done in the Department of Anaesthesia, Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College Hospital, Bangladesh, between July and December of 2019. Purposively selected 147 septic patients with multiple organ failure in Intensive Care Unit were observed prospectively. Serum lactate levels at different intervals were assessed within the first twenty-four hours of recruitment of septic patients. The assigned patients were divided into three lactate variable groups: Group I (mild variable group) – when less than 2 values were not within the target lactate level; Group II (moderate variable group) – when 2-3 values were not within the range; Group III (more variable group) – when more than 3 values were not within the range. Results: The mean age of the study participants was 48.3±12.5years. Among them, 82 (55.78%) were male and 65 (44.22%) were female. Number of survivors and non-survivors in Group I (mild) were 37(84.09%) and 7(15.91%) respectively, while in Group II (moderate) 48(71.64%) and 19(28.36%) respectively and in Group III (more) 13(36.11%) and 23(63.89%) respectively. A highly significant difference (P=0.001) was existed between three blood lactate variability groups with respect to mortality. Logistic regression analysis demonstrated that more lactate variability group had predicted higher mortality rate with a P value of 0.007 and an odds ratio of 16.0. Result is significant. On the other hand, significant effect of moderate lactate variability group on mortality was not found with a P value of 0.665 and an odds ratio of 0.667. Conclusion: The septic patients having more serum lactate variability were reported to have higher mortality rate than that of moderate and less lactate variability in Intensive Care Unit. Our study suggests that serum lactate variability should be included as a future approach to see prognosis and predict mortality in septic patients. Mugda Med Coll J. 2022; 5(2): 71-75